(untitled) (Entrepreneurship Journal for Finance and Business, 2026)
The disparity in employee salaries across different ministries and departments raises questions, discomfort, and feelings of injustice, especially among employees with lower salaries in some ministries compared to their higher-paid counterparts in other ministries. These reasons stem from social factors, followed by economic factors. The prices of goods and services are determined by the size of the employee group with higher salaries, especially if a large group raises the prices of goods and services through their greater purchasing power. Consequently, it becomes difficult for employees with lower salaries to live comfortably, creating economic and social disparities among employee groups. This, in turn, impacts economic and social development. All these reasons prompted me to give great importance to writing this vital and important research, as I focused on analyzing several important indicators, most notably the cost of living index, which measures the minimum cost of living in Iraq, which helps us in formulating a minimum wage policy, and the private sector wage value levels index, which shows the minimum and maximum limits of private sector employee wages according to a labor market survey in the private sector in Iraq, where I concluded that one of the most important factors for labor market stability is the convergence of wages between employees in the private and public sectors, which ends the prevailing reality of the preference of wages for employees in the public sector over their counterparts in the private sector, and we reach a stage of equal demand as much as possible for job opportunities in the two sectors. The index of the total ratio of public sector employees’ salaries to revenues, which shows the high and dangerous percentage that salaries constitute of the country’s total revenues, which must be reduced and controlled, and the index of the ratio of the number of beneficiaries of public sector salaries to the population and labor force, which also constitutes a high percentage, most notably the increase in the number of new appointments that have plunged the country into a state of disguised unemployment and the inclusion of new categories in social welfare salaries, which has burdened the government and forced it to withdraw from the investment budget. In addition to the operating budget for these salaries, the average employee share of the total public sector payroll index (AEI) represents the average salary that should be taken into account when constructing the public sector salary scale. Analyzing these indicators leads us to an important point of convergence that enables us to formulate a clear policy for building a fair and balanced salary system and scale.